2017
DOI: 10.3892/etm.2017.5495
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin‑3‑gallate inhibition of Epstein‑Barr virus spontaneous lytic infection involves downregulation of latent membrane protein 1

Abstract: Abstract. The Epstein-Barr virus (EBV) lytic cycle contributes to the development of EBV-associated diseases. EBV-encoded latent membrane protein 1 (LMP1) is key to EBV lytic replication, and our previous work indicated that epigallocatechin-3-gallate (EGCG) inhibited constitutive EBV lytic infection through the suppression of LMP1-activated phosphoinositide 3-kinase/Akt and mitogen-activated protein kinase kinase/extracellular signal-related protein kinase 1/2 signaling. The present study demonstrated that LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
(79 reference statements)
2
10
0
Order By: Relevance
“…Green tea is one of the most widely consumed teas in the world and is reported to have significant benefits to human health, which is chemically characterized by the presence of high amounts of polyphenolic compounds known as catechins. The most abundant component is epigallocatechin‐3‐gallate (EGCG), which appears to be the primary active ingredient responsible for the biological effects of green tea . EGCG has received much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea is one of the most widely consumed teas in the world and is reported to have significant benefits to human health, which is chemically characterized by the presence of high amounts of polyphenolic compounds known as catechins. The most abundant component is epigallocatechin‐3‐gallate (EGCG), which appears to be the primary active ingredient responsible for the biological effects of green tea . EGCG has received much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant component is epigallocatechin-3-gallate (EGCG), which appears to be the primary active ingredient responsible for the biological effects of green tea. 18,19 EGCG has received much attention in recent years. Previous studies have shown that EGCG exhibits antioxidative, antibacterial, and antitumor effects.…”
mentioning
confidence: 99%
“…Table 5 displays the modulated pathways and their gene counts. The various studies revealed that catechins present in the Camellia sinensis, are the major polyphenols and have a potential role in several viral diseases namely: (HBV) Hepatitis B Virus (Zhong et al 2015), (HSV) Herpes Simplex Virus (Colpitts and Schang 2014), (EBV) Epstein-Barr Virus (Liu et al 2018), Adenovirus (Weber et al 2003), (HIV) Human Immunodeficiency Virus (Yamaguchi et al 2002), (HCV) Hepatitis C Virus (Ciesek et al 2011), (DENV) Dengue Virus (Ismail and Jusoh 2017), (JEV) Japanese encephalitis Virus (Ismail and Jusoh 2017), (ZIKV) Zika virus (Carneiro et al 2016), (TBEV) Tick Borne Encephalitis Virus (Ismail and Jusoh 2017), (CHIKV) Chikungunya Virus (Weber et al 2015), (HTLV-1) Human T cell Leukaemia Virus Type -1 (Harakeh et al 2014), (EV71) Enterovirus 71 (Ho et al 2009), (EBOV) Ebola Virus (Shurtleff et al 2014), (PRRSV) Porcine Reproductive and Respiratory Syndrome Virus (Zhao et al 2014), (VHSV) Hemorrhagic Septicaemia Virus (Estepa 2005), (IHNV) Hematopoietic Necrosis Virus (Estepa 2005), (SVCV) Spring Viremia Carp virus (Estepa 2005) and (GCRV) Grass Carp Reo Virus (Wang et al 2016) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Warm water decoction made by using various species in Ayurveda called ‘ Kashay’ is generally in practice in the prevention of fever, headache, common cold, and inflammation (Tillu et al 2020 ). Similarly, the warm decoction of dry or fresh leaves of Camellia sinensis with or without sugar is also used in daily life style to overcome stress and has been documented for anti-inflammatory, analgesic (De Lima MotaI et al 2015 ) and CNS stimulant activity (Rubab et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also increased apoptosis and enhanced radiosensitivity when a suboptimal dose of radiation was combined with injection of DNAzyme (83). DZ1 caused downregulation of EBV lytic proteins BZLF1 and BMRF1 (84) and reduced luciferase expressing human NPC compared with tumors treated with saline. Efficacy in response to radiotherapy was improved when DZ1 was given as adjunctive therapy to radiotherapy, demonstrating the radiosensitizing effects of DZ1 (61).…”
Section: Targeting Proliferation and Survivalmentioning
confidence: 99%